Patellar tendinopathy in team sports: Preventive exercises - Pena, J.; Moreno-Doutres, D.; Borras, X.; Altarriba, A.; Baiget, E.; Caparros, A.; Busca, B. (Strength and Conditioning Journal, 2017)
Patellar tendinopathy is an overuse injury commonly known as "jumper's knee" that causes pain in the inferior region of the patella. This pathology is recurrent in team sports and has more impact on male athletes. Some anatomical intrinsic factors and several extrinsic factors seem to be key in triggering this condition that is also increasingly appearing in children and adolescents. The aim of this article is to provide coaches and practitioners with some useful practice-based exercises that can be helpful in preventing these disabling tendon injuries in sports such as volleyball, basketball, soccer, American football, and team handball.